L’antropologia in condominio. Pratiche di convivialità attorno a un cortile di Porta Palazzo a Torino - Vietti, Francesco (Antropologia Pubblica, 2024)
The article moves from an auto-ethnographic approach to reflect on spaces and practices of conviviality in a tenement house located in Porta Palazzo, a neighbourhood of Turin characterized by longstanding immigration and cultural diversity. The “biography” of the building mirrors the story of the surrounding area: in the last century, it experienced multiple forms of mobility, hosting internal immigrants from southern Italy, then international immigrants from all over the world and finally a growing number of tourists attracted by its cosmopolitan atmosphere. Today the flats are therefore inhabited by a remarkably diverse population, among whom everyday conflicts, strategic alliances, exchanges and misunderstandings arise about the various dimensions of shared living. Recently, the tenants were engaged by the author in a participative project to collect stories and memories of the house which resulted in the decision to carry out a series of convivial activities in the large courtyard of the building. Analysing the process of (re)generation of social relations observed in this specific context, the article argues that anthropologists should consider the apartment buildings to be a field where they can apply their knowledge to realize initiatives that support inclusion, interaction and solidarity among residents. This is a challenge made even more urgent by the recent lockdown resulting from the Covid-19 epidemic.